EU labour law - Davies, Anne (Cheltenham, 2012)
"The book explores the subject's major policy themes, examines the various procedures by which EU labor law is made, and analyzes key topics such as worker migration, equality, working time and procedures for workers' participation in employers' decision-making. It sets the legal materials in their policy context and identifies the important issues which have shaped the development of EU labor law and are likely to determine its future, including the economic crisis and the debate about fundamental rights in the EU.